Analysis of risk factors related to nonalcoholic fatty liver disease: a retrospective study based on 31,718 adult Chinese individuals - Wang, Ganggang; Shen, Xiaowei; Wang, Yicun; Lu, Huanhua; He, Hua; Wang, Xiaoliang (Frontiers in Medicine, 2023)
Objective Nonalcoholic fatty liver disease (NAFLD) is becoming increasingly prevalent worldwide. This study guides the prevention and diagnosis of NAFLD by analyzing its risk factors and the diagnostic value of each index for NAFLD. Method We collected the clinical information of adults individuals who underwent physical examination in the Physical Examination Center of Qingpu Branch of Zhongshan Hospital, Fudan University, from January 2016 to January 2020, including gender, age, body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin (TBIL), direct bilirubin (DBIL), indirect bilirubin (IBIL), fasting blood glucose (FBG), total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL). We performed logistic regression analysis and ROC diagnostic analysis. Results The results showed that age, BMI, SBP, ALT, AST, FBG, TBIL, TG, and LDL were risk factors for NAFLD in adults, and HDL was a protective factor (all p-values were less than 0.05). Among them, age, BMI, ALT, TG, and HDL had a predictive value for the occurrence of NAFLD in the adults (AUC = 0.708, 0.836, 0.767, 0.780, and 0.732, respectively). The combination of age, BMI, ALT, TG, and HDL had a diagnostic value for the occurrence of NAFLD (AUC = 0.881). Conclusion Healthy people should pay attention to their BMI levels, manage blood pressure, blood glucose, and lipid levels, and pay attention to changes in ALT and AST index levels to prevent NAFLD. Age, BMI, ALT, TG, and HDL indexes are helpful factors in the diagnosis of NAFLD.